2017
DOI: 10.3389/fmicb.2017.01470
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of the Microbiota of Donor Human Milk with Mother’s Own Milk

Abstract: The American Academy of Pediatrics recommends that extremely preterm infants receive mother’s own milk (MOM) when available or pasteurized donor breast milk (DBM) when MOM is unavailable. The goal of this study was to determine whether DBM could be inoculated with MOM from mothers of preterm infants to restore the live microbiota (RM). Culture dependent and culture independent methods were used to analyze the fluctuations in the overall population and microbiome, respectively, of DBM, MOM, and RM samples over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
70
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 61 publications
(72 reference statements)
11
70
1
1
Order By: Relevance
“…Some authors postulate that preterm infants fed DHM or formula are devoid of contact with HMM [79], and for this reason strategies which allow an early exposure of preterm infants to the HMM have been proposed. To this purpose, Cacho et al [80] inoculated DHM with small amounts of MOM from mothers of preterm infants. According to viable cell counts and microbiome analysis, they suggested that DHM incubated with 10% MOM for 4 h was a reasonable restoration strategy.…”
Section: Human Milk Microbiota: Implications For Preterm Infants' Carmentioning
confidence: 99%
“…Some authors postulate that preterm infants fed DHM or formula are devoid of contact with HMM [79], and for this reason strategies which allow an early exposure of preterm infants to the HMM have been proposed. To this purpose, Cacho et al [80] inoculated DHM with small amounts of MOM from mothers of preterm infants. According to viable cell counts and microbiome analysis, they suggested that DHM incubated with 10% MOM for 4 h was a reasonable restoration strategy.…”
Section: Human Milk Microbiota: Implications For Preterm Infants' Carmentioning
confidence: 99%
“…Preterm infants fed donor milk had gut microbiomes that more closely resembled infants fed their mother's own milk compared with formula fed infants (Parra‐Llorca et al, ). In addition, some groups have tested the viability of “spiking” donor milk with infants' own mothers milk to inoculate the infants with a personalized microbiome (Cacho et al, ), a concept similar to a recent push to include probiotics in infant formula (Aceti et al, ; Cavallaro, Villamor‐Martínez, Filippi, Mosca, & Villamor, ; Mugambi, Musekiwa, Lombard, Young, & Blaauw, ; Rautava et al, ; Villamor‐Martínez et al, ). These interventions showcase the importance of breastfeeding, or in lieu of breastfeeding, a diet reflecting the myriad of components maternally transferred that support the development of the offspring's immune system and shape gut homeostasis during early life.…”
Section: Nongenetic Inherited Influences Directly On the Immune Systemmentioning
confidence: 99%
“…18 A recent study demonstrated that incubation of donor milk with 10% of mothers' own milk for 4-8 hours resulted in microbe levels similar to those seen in mothers' own milk. 18 Alternative pasteurization techniques, such as ultraviolet C radiation, can be developed that help preserve the essential bioactive components that are lost in the processing of donor milk. 19 Because many aspects of donor milk are suboptimal for preterm infants, there is a theoretical rationale for preferring mothers' own milk over banked donor milk; however, well-designed randomized controlled studies are needed to further evaluate the benefits of mothers' own milk and donor milk in preterm infants.…”
mentioning
confidence: 98%
“…Compared with donor milk, mothers' own milk has a higher concentration of most microbes and differs in the relative abundance of bacterial genera. 18 Mothers' own milk could potentially be used to personalize the microbiota of donor milk. 18 A recent study demonstrated that incubation of donor milk with 10% of mothers' own milk for 4-8 hours resulted in microbe levels similar to those seen in mothers' own milk.…”
mentioning
confidence: 99%
See 1 more Smart Citation